Review—Organic Materials for Thermoelectric Energy Generation. (28th January 2017) - Cowen, Lewis M.; Atoyo, Jonathan; Carnie, Matthew J.; Baran, Derya; Schroeder, Bob C.
Abstract : Organic semiconductor materials have been promising alternatives to their inorganic counterparts in several electronic applications such as solar cells, light emitting diodes, field effect transistors as well as thermoelectric generators. Their low cost, light weight and flexibility make them appealing in future applications such as foldable electronics and wearable circuits using printing techniques. In this report, we present a mini-review on the organic materials that have been used for thermoelectric energy generation.